Electrochemical properties of titanium nitride nerve stimulation electrodes: an in vitro and in vivo study - Meijs, Suzan; Fjorback, Morten; Jensen, Carina; Sørensen, Søren; Rechendorff, Kristian; Rijkhoff, Nico J. (Frontiers in Neuroscience, 2015)
The in vivo electrochemical behavior of titanium nitride (TiN) nerve stimulation electrodes was compared to their in vitro behavior for a period of 90 days. Ten electrodes were implanted in two Göttingen minipigs. Four of these were used for electrical stimulation and electrochemical measurements. Five electrodes were kept in Ringer’s solution at 37.5 °C, of which four were used for electrical stimulation and electrochemical measurements. The voltage transients measured in vivo were 13 times greater than in vitro at implantation and they continued to increase with time. The electrochemical properties in vivo and the tissue resistance (Rtissue) followed a similar trend with time. There was no consistent significant difference between the electrochemical properties of the in vivo and in vitro electrodes after the implanted period. The differences between the in vivo and in vitro electrodes during the implanted period show that the evaluation of electrochemical performance of implantable stimulation electrodes cannot be substituted with in vitro measurements. After the implanted period, however, the performance of the in vivo and in vitro electrodes in saline was similar. In addition, the changes observed over time during the post-implantation period regarding the electrochemical properties of the in vivo electrodes and Rtissue were similar, which indicates that these changes are due to the foreign body response to implantation.